Penerapan Green Corporate Social Responsibility (CSR) di Hotel Hyatt Regency Yogyakarta melalui Program â€œGreen Jogjaâ€ - Yeni Rosilawati; Affan Arsyad (Universitas Ahmad Dahlan, 2019)
Green Corporate Social Responsibility )Green CSR( is the companyâ€™s commitment to be responsible for the environment and the preservation ofthe surrounding environment, especially those a ected by the companyâ€™s operations. The purpose of this study is to evaluate the program of Green CSR of the Hyatt Regency Yogyakarta. The study was qualitative designed as a case study. The data were obtained from primary data through in-depthinterviews with CSR managers and local communities around the hotel and secondary data in the form of reports on CSR activities in the mass media. The results showed that the Green CSR programs of Hyatt Regency Jogja included(i) using treated hotelâ€™s wa ewater for watering plants, (ii) replacing 80% ofhotel lights with LED lights, )iii( using solar panels and saving energy through third party laundry which was proven to reduce the electricity usage of the hotel, )iv( holdingÂ Garden Adoption, the competition to decorate the garden in each employeeâ€™s house, and )v( empowering the community around the hotel through education to increase the awareness on the environment withsome vandalism purging and tree planting activities to support the su ainableenvironmental development in Yogyakarta.